MicroRNA-206 Regulation of Skin Pigmentation in Koi Carp (Cyprinus carpio L.) - Dong, Zaijie; Luo, Mingkun; Wang, Lanmei; Yin, Haoran; Zhu, Wenbin; Fu, Jianjun (Frontiers in Genetics, 2020)
MicroRNAs (miRNAs) are ~22 nucleotide non-coding RNA molecules that act as crucial roles in plenty of biological processes. However, the molecular and cellular mechanisms of miRNAs to regulate skin color differentiation and pigmentation in fish have not been fully understood. Herein, we revealed that miR-206, a skin-enriched miRNA, regulates melanocortin 1 receptor (mc1r) expression by binding to its 3’-untranslated (UTR) region through bioinformatics and luciferase reporter assay in koi carp (Cyprinus carpio L.). The analysis of spatial and temporal expression patterns suggested that miR-206 is a potential regulator in the skin pigmentation process. Then, we silenced it in vivo with an antagomir method; the result showed a substantial increase of mc1r mRNA expression and protein level, and also its downstream genes, including tyrosinases (tyr) and dopachrome tautomerase (dct). Moreover, we constructed the miRNA-206 sponge lentivirus vector to transfect koi carp melanocytes in vitro, further checked the functions of melanocytes using Cck-8 and Transwell assays. As a result, inhibition of miR-206 significantly up-regulated mc1r mRNA expression and protein level and accelerated the melanocytes proliferation and migration ability compared with the scrambled-sequence negative control group (miR-NC). These findings would facilitate understanding the molecular regulatory mechanisms underlying miRNA-mediated skin color pigmentation in koi carp.